2017
DOI: 10.1002/term.2412
|View full text |Cite
|
Sign up to set email alerts
|

Bone tissue engineering in oral peri-implant defects in preclinicalin vivoresearch: A systematic review and meta-analysis

Abstract: The regeneration and establishment of osseointegration within oral peri-implant bone defects remains a clinical challenge. Bone tissue engineering (BTE) is emerging as a promising alternative to autogenous and/or biomaterial-based bone grafting. The objective of this systematic review was to answer the focused question: in animal models, do cell-based BTE strategies enhance bone regeneration and/or implant osseointegration in experimental peri-implant defects, compared with grafting with autogenous bone or onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 81 publications
1
23
0
2
Order By: Relevance
“…The addition of bioactive agents and growth factors has been proposed to enhance the bone regenerative outcomes. In fact, the addition of bone morphogenetic proteins (BMPs) has shown promising results when combined with guided bone regeneration, in terms of promoting additional bone formation when compared with the scaffold alone (Jung, Thoma, & Hammerle, 2008;Kelly, Vaughn, & Anderson, 2016;Shanbhag, Pandis, Mustafa, Nyengaard, & Stavropoulos, 2018). When this principle has been applied to the treatment of experimental peri-implantitis, two studies have assessed the added benefit of adding rhBMP-2 to a vehicle carrier.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of bioactive agents and growth factors has been proposed to enhance the bone regenerative outcomes. In fact, the addition of bone morphogenetic proteins (BMPs) has shown promising results when combined with guided bone regeneration, in terms of promoting additional bone formation when compared with the scaffold alone (Jung, Thoma, & Hammerle, 2008;Kelly, Vaughn, & Anderson, 2016;Shanbhag, Pandis, Mustafa, Nyengaard, & Stavropoulos, 2018). When this principle has been applied to the treatment of experimental peri-implantitis, two studies have assessed the added benefit of adding rhBMP-2 to a vehicle carrier.…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled studies (UT) and cases reports (with ≥3 patients) of cell‐based BTE were also identified to capture possible relevant information regarding cell sources, delivery strategies, and adverse events, although data regarding bone regeneration from these studies were not considered for the meta‐analyses. Sampling of pre‐clinical data was limited to large‐animal models and regards mainly an update of our previously published reviews (Shanbhag et al., , ). These data were only included to compare with the clinical data, which is the focus of the present review.…”
Section: Methodsmentioning
confidence: 99%
“…The cells can be harvested by minimally, and relatively less, invasive techniques (compared to AB harvesting) from various tissues, most commonly bone marrow and adipose tissues, under local anaesthesia, and without the need for hospitalization. Thus, BTE strategies are indeed emerging as promising alternatives to AB and/or biomaterial‐based grafting, as demonstrated by several pre‐clinical and some clinical studies (for reviews, see Janssen et al., ; Padial‐Molina et al., ; Shanbhag et al., 2015; Shanbhag, Pandis, Mustafa, Nyengaard, & Stavropoulos, , ; Miguita, Mantesso, Pannuti, & Deboni, ). Among these BTE strategies, three main interventions using cell therapies have been tested: (a) use of “minimally manipulated” whole tissue fractions; (b) use of more‐than‐minimally manipulated or ex vivo expanded uncommitted stem/progenitor cells; and (c) use of ex vivo expanded committed bone‐derived cells.…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterials play an important role in bone regenerative strategies [ 1 ] in both orthopedics and dentistry as scaffolds [ 2 ] or as a support for prosthesis, e.g., hip or dental implants [ 3 ]. In all these clinical situations the challenge biomaterials must face is to integrate in the host and promote bone healing along its surfaces [ 4 ], albeit with noticeable differences.…”
Section: Biomaterials and Bone Regenerationmentioning
confidence: 99%